Integration of Knowledge and Religion in the Perspective of Islamic Education: A Comparative Study of the Thoughts of Al-Attas and Fazlur Rahman - Hasanah, Muwahidah Nur; Idharudin, Abdul Jabar; Bermi, Wibawati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2025)
Contemporary Islamic education is facing a serious challenge in the form of a dichotomy between religious and secular sciences, which has led to an epistemological crisis and moral decline in the learning process. The integration of knowledge and religion has become an urgent agenda in order to develop an educational system that is not only rational and scientific but also spiritual and ethical. This study aims to critically analyze and compare the ideas of integration of knowledge and religion in the thoughts of two major Muslim scholars: Syed Muhammad Naquib al-Attas and Fazlur Rahman, and to assess their relevance to the development of Islamic education in Indonesia. This research uses a qualitative approach through library research, focusing on primary and secondary works by both scholars, as well as supporting literature in Islamic education, Islamic epistemology, and integrated knowledge. The data were analyzed using descriptive-comparative methods to reveal the similarities, differences, and educational implications of their ideas. The findings show that Al-Attas emphasizes the Islamization of knowledge and the cultivation of adab (ethics) as the foundation of integration, using a metaphysical and normative approach. In contrast, Fazlur Rahman promotes a hermeneutical-contextual methodology through his double movement theory, highlighting ethical interpretation and the response of revelation to social reality. Despite their different approaches, both agree on the urgency of integrating knowledge and religion to form a holistic human being (insān kāmil) in Islamic education. This study concludes that the integration models of Al-Attas and Rahman are highly relevant for addressing the dualism in Indonesia’s Islamic education system. It is therefore recommended that their concepts be selectively and contextually adopted in curriculum development, teacher training, and the formulation of educational visions based on adab, ethics, and epistemological integrity.